Nauka i filozofia w bajkach George Sand na przykładzie tekstów wybranych z tomiku bajek "Mówiący dąb. Opowiadania babuni" - Kaczka, Piotr (Acta Neophilologica, 2024)
The purpose of this article is to show how multifaceted the fairy tales of George Sand are in terms of scientific and literary testimony. In addition, it demonstrates how the multifaceted nature of the prose makes it possible to put a different complexion on than previously: as a fabulist, rather than a heroine of 19th century scandals. By examining previous studies and relying on my own research. I present the interdisciplinary nature of the texts and the scientific theories and philosophical elements hidden in them, such as evolutionism, catastrophism, saintsimonism, socialism and reincarnation. By contextualizing and exploring autobiographical themes, the novelty and pioneering nature of Sand’s fairy tales is confirmed. Additionally, an important aspect here is the audience to whom the writer addresses her texts.